Argent Street North [Broken Hill, New South Wales] - Idriess, Ion L. (Ion Llewellyn), 1890-1979. (1888)
"Argent St Broken Hill looking north 12.3.88 no 8"--text on lower left of image.
Condition: Poor.
Part of collection: Ion Idriess glass plate negative collection.
Title from caption in: The silver city.
Upper left image of a group of four (PIC/8807/64-PIC/8807/67) on a single plate.
On plate with: The silver city grows -- Jamieson's shaft no 51 -- Oxide Street.
Also available online
Keywords: Broken Hill (N.S.W.) -- Photographs